Prevalence of Pathogenic Bacteria Isolated from Two Selected Salad Vegetables and Antibiogram Profile of Klebsiella spp. (The Agriculturists, 2016)
The study was conducted to examine microbiological quality of raw salad vegetables of Jessore city of Bangladesh. Fourteen samples of two types of vegetables which are commonly used for salad eg. Tomato (Lycopersicum esculentum) and Cucumber (Cucumis sativus) were collected from different local markets of Jessore City and their bacteriological attributes were investigated using routine methods. All the vegetables were highly contaminated with coliforms and fecal coliforms. Range of Total Viable Count were 11x106 CFU/g to 20x107 CFU/g for tomato and 12x105 CFU/g to 24x107 CFU/g for cucumber, Total Coliform Count were 11x104 CFU/g to 2 x106 CFU/g for tomato and 10.2x103 CFU/g to 60x104 CFU/g for cucumber and Total Staphyllococcal Count were 11x104 CFU/g to 25x106 CFU/g for tomato and 10x104 CFU/g to 50x106 CFU/g for cucumber. Total coliforms were identified as Escherichia coli, Klebsiella spp., Enterobacter spp., Citrobacter spp. and Shigella spp. Antibiogram was conducted with twelve different antibiotics for some randomly selected pure colonies of Klebsiella spp. Multidrug resistance was observed in 90% isolates with resistance from two to six antibiotics. Hygienic practices should be followed in handling the vegetables in local markets and vegetables might have an important role as a source of antibiotic resistant bacteria.The Agriculturists 2015; 13(1) 9-17